Analysis heating and cooling by water in injection molding for different products - Huỳnh Đỗ Song Toàn; Trần Minh Thế Uyên; Võ Bá Anh Đại; Lê Hiếu Giang (Journal of Technical Education Science, 2015)
Currently, there are many research results to optimize the mold temperature. However, the analysis of heating and cooling by water injection molding is not yet enough for reference. The outcomes of this paper include a complete analysis of heat transfer in plastic injection molds using water for heating and cooling. This method is able to increase the mold temperature from 30 0C to 63.50C in 20s for the heating step and decrease the mold temperature to 350C in the next 20s for the cooling step. Also, the errors when performing simulation are examined. Finally, the analysis of heat transfer in mold for different products is performed.